Rekonstruksi Instrumen Tes Perbuatan Teks Hikayat pada Siswa Kelas X Bermuatan Literasi Membaca (Assesmen Kompetensi Minimum) - Dina Purnama Sari; Sulistia Ellsa; Wagiran Wagiran; Deby Luriawati Nuryatmojo (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2021)
The development of the education system in the 21st century demanded change in all aspects. Determination of Minimum Competency Assessment (AKM) has the impact of changes in the implementation of the learning evaluation process. The implementation of AKM in the education system applies to all subjects, including Bahasa Indonesia. One of the components related to the learning of Bahasa Indonesia precisely the learning of Expression Of Writing Literature is AKM Literacy. The limitation of the resources and test instruments in the implementation of learning evaluation becomes a problem that needs to be addressed wisely and immediately because it will affect the achievement of learning objectives. The purpose of this study is 1) describe the analysis of the error of the instrument of the test of deeds in the Indonesian Language Student Book Grade XI SMA which is charged with AKM reading literacy, and 2) describe the reconstruction of the error of the test instrument in the Book of Indonesian Language Students grade XI high school loaded with AKM reading literacy. The method used is descriptive qualitative with the model of literature and literature studies as well as strengthening through documentation and field observation. The results of this study showed that based on the results of the analysis of the test instrument there are several components that are not yet appropriate which include material aspects, construction aspects, and language aspects. As well as attaching the reconstruction results by making improvements to the test of the act of developing the text of the saga on the aspects of material, construction, language and improving reading literacy on the question.